Effective bandgap tuning with non-trivial modulation in room temperature magnetic and electrical responses of low level Ba–Cr co-substituted BiFeO3 nanoparticles. Issue 14 (15th July 2022) - Hoque, M.M.; Islam, M.T.; Islam, M.R.; Zubair, M.A.
Abstract: This work reports the effects of low-level Ba(5%)-Cr(1–5%) co-incorporation on room temperature structural and functional properties of sol-gel synthesized bismuth ferrite ( BiFeO 3 ) nanoparticles. Within this co-substitution limit, structural stability of the main perovskite phase with rhombohedral ( R 3 c ) symmetry was enhanced by Ba substitution. The defect chemical and crystallographic modifications together brought about by the low level co-substitution considerably reduced the BiFeO 3 nanoparticle's optical bandgap by ∼23% to 1.59 eV. An enhanced saturation magnetization (∼3.6 emu/g) observed in BiFeO 3 was further raised by ∼ 100% through 5% Ba–Cr co-incorporation. This significant improvement in the magnetic property of the materials, recognized to be composed of single domain non-interacting nanoparticles was attributed to an enhanced super-exchange interaction phenomenon, and was further corroborated by the contributions from the deconvoluted magnetic components associated with different microstructural phases. The defect assisted variation in leakage current culminates in lossy dielectric type polarization-hysteresis responses. The origin of the leakage current was analyzed in terms ohmic, SCLC and Pool-Frankel emission mechanisms. Technically these observed developments in the functional responses of low level Ba–Cr co-substituted BiFeO3 nanoparticles, brought about by the structural and microstructural modifications open a potential window for photo-chemical/electric and magnetic applications.